2015
DOI: 10.1039/c5ob01002k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and conformational studies of chiral macrocyclic [1.1.1]metacyclophanes containing benzofuran rings

Abstract: Macrocyclic [1.1.1]metacyclophanes (MCPs) containing benzene and benzofuran rings linked by methylene bridges and which can be viewed as calixarene analogues, have been synthesized by demethylation of [3.3.1]MCP-diones with trimethylsilyl iodide (TMSI) in MeCN. The [3.3.1]MCP-diones are synthesized by using (p-tolylsulfonyl)methyl isocyanide (TosMIC) as the cyclization reagent in N,N-dimethylformamide (DMF) with an excess of sodium hydride. (1)H NMR spectroscopy revealed that the remaining hydroxyl group on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 105 publications
0
9
0
Order By: Relevance
“…We previously reported the synthesis of calix[3]benzofurans which are unusual macrocycles bearing benzofuran units instead of only benzene rings. Recently, our group illustrated an efficient intramolecular cyclization synthetic route to produce macrocyclic [1.1.1]MCPs containing two and three benzofuran rings, using( p ‐tolylsulfonyl)methyl isocyanide (TosMIC) as the cross‐coupling cyclization reagent. In an analogous manner, the synthesis of 6,15,24‐tri‐ tert ‐butyl‐9,18,27‐trimethoxy[3.3.3]‐MCP‐2,11‐dione 5 was previously reported and is shown in Scheme .…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…We previously reported the synthesis of calix[3]benzofurans which are unusual macrocycles bearing benzofuran units instead of only benzene rings. Recently, our group illustrated an efficient intramolecular cyclization synthetic route to produce macrocyclic [1.1.1]MCPs containing two and three benzofuran rings, using( p ‐tolylsulfonyl)methyl isocyanide (TosMIC) as the cross‐coupling cyclization reagent. In an analogous manner, the synthesis of 6,15,24‐tri‐ tert ‐butyl‐9,18,27‐trimethoxy[3.3.3]‐MCP‐2,11‐dione 5 was previously reported and is shown in Scheme .…”
Section: Resultsmentioning
confidence: 82%
“…The 1 H‐NMR signal patterns for 6 a shows that it is highly flexible in solution at room temperature and undergoes very fast conformational change. Previously, in the case of the symmetrical 1 5 ,3 5 ,5 5 ‐tri‐ tert ‐butyl‐1 2 ‐hydroxy‐1‐(1,3)‐benzena‐3,5(2,7)benzo‐furanacyclohexaphane, we had observed a calix[4]arene‐like cone conformation in both the solution and solid states . Dynamic ‘H‐NMR spectroscopy of 6 a showed that the protons of the Ar CH 2 Ar methylene group each appeared as a singlet, even down to –60 °C (CDCl 3 /CS 2 1:3) and thus its rate of conformational ring flipping is faster than the NMR time scale above this temperature.…”
Section: Resultsmentioning
confidence: 99%
“…6,15,22-Tri-tert-butyl-9,18,25-trimethoxy[3.3.1]metacyclophane-2,11-dione 3 was synthesized by the coupling reaction of TosMIC adduct 1 with 2 according to the reported procedure [37]. , and triethylene glycol (5 mL) was heated at 120 C for 2 h and then at 200 C for 3 h. The cooled mixture was poured into water (50 mL), acidified with diluted HCl, and extracted with CH 2 Cl 2 (5 Â 30 mL), washed with water (2 Â 20 mL), dried over Na 2 SO 4 , and concentrated under reduced pressure.…”
Section: Methodsmentioning
confidence: 99%
“…The demethylation of [3.3.1]MCP-dione 19 in acetonitrile with in-situ-generated TMSI produced a mixture of benzofuran ring-containing products, the symmetrical 22a and unsymmetrical 23a and a new spirobisdihydro-furan 24 in 24 , 45 and 5% yields, respectively ( Figure 6 ) [ 39 ]. It is presumed that the trihydroxy-diketo intermediate 21 is first formed, and then undergoes intramolecular TMSI-mediated cyclizations to form the observed products [ 39 , 40 , 41 ]. Sawada and co-workers had previously reported that the treatment of tetramethoxy [2.1.2.1]MCPs with TMSI formed hemisphere-shaped calixarene analogues containing a dihydrobenzofuran ring [ 42 , 43 ].…”
Section: Calixbenzofuran-analogous Mcps: Calix[3]benzofuran Analogmentioning
confidence: 99%
“…All hydrogens except methoxy and phenolic hydrogens are omitted for clarity. Figure adapted and re-calculated from [ 39 ].…”
Section: Figures Schemes and Tablementioning
confidence: 99%